Pacman Game Benefit Analysis on Decision Making Speed - Wulandari, Wati; Harnadi, Bernardinus (Soegijapranata Catholic University, 2014)
Pacman game is able to train the child concentration and decision making speed. This Research use respondent children ages 6 up to11 years as a player who will take the data. Every respondent must play Pacman game and then they can answer 10 questions. Resulting data are analyzed with a statistical method; it is âproduct moment